A synthesis of language learning strategies: current issues, problems and claims made in learner strategy research - Barjesteh, Hamed; Mukundan, Jayakaran; Vaseghi, Reza (Australian International Academic Centre, 2014)
The current paper presented theoretical assumptions behind language learning strategies (LLS) and an overview of methods used to identify learners’ strategies, first, and then summarized what have been reported from large number of descriptive studies of strategies by language learners. Moreover, the paper tried to present the variety of definitions and classifications of learning strategies can be counterproductive in a number of ways. Finally, the researchers argued that in spite of the lack of coherence and clarity in the description of second language learning strategies, the relevant research findings can be profitably incorporated into classroom activities and that further research and application in this area can make our understanding of learning strategies deeper and our facilitation of language learning more fruitful.